Hearts in sight – A pretty picture of collapse and excellence - Smit, Francis E. (SA Heart Journal, 2017)
A surprising number of serious decisions in the history of nations and populations have been firmly based upon generalisations, speculation, popular opinion and unproven theories. It is very much like guessing the weight and height of a patient and then calculating his body surface area to the second decimal, like old perfusionists did, and then basing the required pump flow rates on this calculation. The funny thing is that the patients were mostly fine. So, I trust that most of you will survive the generalisations and opinions expressed in this editorial.